IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN NAGA PITA, KECAMATAN SIANTAR MARTOBA, KOTA PEMATANGSIANTAR - Tanjung, Elsa Susanna Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Slum-Free City Program (KOTAKU) is a national program that aims to improve access to infrastructure and basic services in urban slums. This research was conducted in Naga Pita Village, Siantar Martoba District, which is also one of the areas implementing the KOTAKU program in Pematangsiantar City. The purpose of this study was to determine and provide an overview of the Implementation of the KOTAKU Program and identify inhibiting factors in implementing the KOTAKU Program. This study uses a qualitative approach with descriptive methodology. The focus of the study is based on the theory of Van Meter and Van Horn which includes policy standards and objectives, resources, organizational linkages, characteristics of implementers, socio-economic situations, and attitudes. The informants of this study were the Head of the Naga Pita Village, Village Section, KOTAKU Members, and local residents. Data collection techniques used were recording, interviews, and observations. The results of the study indicate that the KOTAKU Program is being implemented in Naga Pita Village, Siantar Martoba District, Pematangsiantar City. Related to: (a) road maintenance, the government has carried out road repairs well through the KOTAKU program; and (b) factors that influence the implementation of the KOTAKU program, such as public awareness and interest in the Slum-Free City initiative.